Sortes in Practice: Constructing Contexts for the Use of Sortilege Materials in Late Antique Christianity - Childers, Jeff W. (Early christianity, 2025)
Although divination was common in the ancient world, our understanding of how the most common divinatory practices typically worked for the client or inquirer is very limited. In the case of text-based divination, we get some clues about usage from the instructions that accompany the tools, as with the Sortes Astrampsychi. Yet many tools have no such aids, as is the case with the distinctly Christian book on which this study focuses: a sixth-century Syriac biblical manuscript designed for divination. This study analyzes the specific features of the book in question in light of late antique divinatory practice, putting the analysis into conversation with anthropological studies of contemporary divination - studies that emphasize the significance of the relationship between clients and practitioners rather than the mechanisms of ritual - in order to depict more clearly how late antique Christian text-based divinization actually worked in context.